Synthesis of Poly(2-Acrylamido-2-Methylpropane Sulfonic Acid) and its Block Copolymers with Methyl Methacrylate and 2-Hydroxyethyl Methacrylate by Quasiliving Radical Polymerization Catalyzed by a Cyclometalated Ruthenium(II) Complex - Vanessa Martínez-Cornejo (Polymers, 2020)
The first example of quasiliving radical polymerization and copolymerization of 2-acrylamido-2-methylpropane sulfonic acid (AMPS) without previous protection of its strong acid groups catalyzed by [Ru(o-C6H4-2-py)(phen)(MeCN)2]PF6 complex is reported. Nuclear magnetic resonance (RMN) and gel permeation chromatography (GPC) confirmed the diblock structure of the sulfonated copolymers. The poly(2-acryloamido-2-methylpropanesulfonic acid)-b-poly(methyl methacrylate) (PAMPS-b-PMMA) and poly(2-acryloamido-2-methylpropanesulfonic acid)-b-poly(2-hydroxyethylmethacrylate) (PAMPS-b-PHEMA) copolymers obtained are highly soluble in organic solvents and present good film-forming ability. The ion exchange capacity (IEC) of the copolymer membranes is reported. PAMPS-b-PHEMA presents the highest IEC value (3.35 mmol H+/g), but previous crosslinking of the membrane was necessary to prevent it from dissolving in aqueous solution. PAMPS-b-PMMA exhibited IEC values in the range of 0.58–1.21 mmol H+/g and it was soluble in methanol and dichloromethane and insoluble in water. These results are well correlated with both the increase in molar composition of PAMPS and the second block included in the copolymer. Thus, the proper combination of PAMPS block copolymer with hydrophilic or hydrophobic monomers will allow fine-tuning of the physical properties of the materials and may lead to many potential applications, such as polyelectrolyte membrane fuel cells or catalytic membranes for biodiesel production.